Design strategy for an analyte-compensated fluorescent probe to reduce its toxicity. Issue 65 (26th July 2022) - Zhang, Jinlong; Mu, Shuai; Wang, Weilin; Sun, Huipeng; Li, Shuangqin; Shi, Xuezhao; Liu, Yunbo; Liu, Xiaoyan; Zhang, Haixia
Abstract : During biological detection, the toxicity caused by probes to living organisms is neglected. In this study, an analyte-compensated fluorescent probe (NP-SN3 ) was constructed for the detection of H2 S. Abstract : During biological detection, the toxicity caused by probes to living organisms is neglected. In this study, an analyte-compensated fluorescent probe (NP-SN3 ) was constructed for the detection of H2 S. Through experiments with HepG2 cells and zebrafish embryos and larvae, the NP-SN3 probe showed no significant difference in imaging performance compared with the traditional probe (NP-N3 ) but exhibited lower detection-induced toxicity in the imaging of liver fibrosis in activated HSC-T6 cells. During the development of zebrafish embryos and continuous administration in rats, NP-SN3 showed a lower death rate, higher hatchability and lower malformation in zebrafish embryos and milder pathological symptoms in stained rat tissues.